THE INTERACTION OF BRIDGE STRUCTURES WITH MOVING LOADS - Marochka, V. V. (Science and Transport Progress, 2004)
Often is collided at designing and operation of bridges of gapped systems with excessive oscillations of superstructures under a temporary load. On the other hand, there are some number of extinguishers constructions, which can be reduced to abutment dampers. Calculation of such structures is considered in this article.